A Retrospective Cohort Study of Total Colonic Aganglionosis: Is the Appendix a Reliable Diagnostic Tool? - Reck-Burneo, Carlos Albert; Lane, Victoria; Vinay, Prasad; Wood, Richard; Levitt, Marc (Journal of Neonatal Surgery, 2016)
Please see Fulltext